Perhitungan Harga Pokok Produksi melalui Metode Full Costing untuk Penetapan Harga Jual Produk Pet Feeder - Fardillah, Frena; Singgih, Restu (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2023)
Development world effort and world industry this modern era experience enough development _ fast , wrong one impact fast development in world effort that is the number of perpetrators continuous effort continuously popping up both Micro and Small Enterprises Medium (MSME) and company big . Calculation price tree production very play a role important in determination price sell a product so that price offered _ could compete with perpetrator other effort , lack experience and knowledge in field accountant cost , usually perpetrator effort micro small and medium in calculation cost price tree production nor price tree sale based on estimate or estimation course . Study this aim for knowing price tree production with use method full cost To use determine price sell product pet feeders . Study this use method full cost is method determination cost production that counts all element cost production into the cost production consisting of from cost ingredient raw , cost power work , cost overheads . After conducted calculation a number of cost like cost ingredient raw , cost power work and cost overhead factory , then produce price tree production and price tree sales , on determination price selling per business unit micro small and medium icung suck lovebirds set 20% profit from price per unit already calculated with use method full cost.Keywords: Price tree production , full costing , pet feeder, UMKM, price tree sale